PO 8470 First independent assessment of pharmaceutical company action on AMR. (24th April 2019) - Kisakye, Jacqueline; Knoeff, Josefien; Ruiz, Adrian; Calcada, Dulce; Iyer, Jayasree; Gabrielle Breugelmans, J
Abstract : Background: Antimicrobial resistance (AMR) is one of the most significant threats to public health globally. It will worsen without concerted efforts to spur the development of new antibiotics and ensure access and stewardship of existing ones. Pharmaceutical companies have a critical role to play in these efforts. The Access to Medicine Foundation developed the AMR Benchmark to measure how pharmaceutical companies are responding to AMR and to share and push best practices within the industry. Methods: The AMR Benchmark assessed the AMR activities of 30 pharmaceuticalcompanies in 106 low- and middle-income countries. Survey data on company activities were collected across three research areas: research and development (R&D); manufacturing and production; and access and stewardship. For each research area, specific metrics were developed to evaluate company performance. These metrics were defined through consultation with experts working across the AMR field and represent a broad consensus on where companies can and should be taking action to limit AMR. Results: The Benchmark found that there are good practices in all research areas. Out of 276 R&D projects targeting infectious diseases, 175 target pathogens identified as priority by WHO/CDC. Of these, 88 are in preclinical stage, 87 are in clinical stage, and 54 target gram-negative bacteria. Out of 28 antibiotics in late clinical stage, only two have access and stewardship plans in place. Nearly half of companies evaluated are involved in AMR surveillance and eight companies set limits on antibiotic wastewater discharge. Lastly, four companies separate sales agent bonuses from antibiotics sales volumes to reduce overuse of antibiotics. Conclusion: The Benchmark identified the good ideas being implemented by companies to limit AMR and mapped opportunities to amplify current efforts. Although companies are taking some action, the R&D pipeline needs to be further strengthened and candidates reaching late clinical stage must be supported by concrete plans to ensure access and stewardship.